A Study on Dependence of Size of Business on Profile of Women Entrepreneurs in the State of West Bengal: Exploring the Influence of Business Size on Women Entrepreneurs in West Bengal (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Women entrepreneurs have been making a remarkable impact in all segments of the economy. Strong desire to do something positive brings valuable position in their society and family. Women entrepreneurship has gained momentum in last three decades rapidly increasing the number of women entrepreneurs and their contribution towards economic growth. Women play very important role in building up the backbone of India’s economy. Women have the ability to balance the different tasks and priorities and tend to have satisfaction and success in it and build a relationship with employees and customers. They are the controller of their own destiny and doing something that is worthwhile. They have the potential to manage and control the business of their own. These qualities and strengths of women are found very productive in their business channels. This paper seeks to identify various factors which affect the development motivate the women entrepreneur. The profile of women entrepreneur also been studied which depend on size of business. This study has been conducted on 250 sample respondents in the five districts 1. Kolkata. 2. Howrah. 3. South 24 Parganas. 4. North 24 Parganas 5. Hooghly in the state of West Bengal. This paper highlights the profile of women entrepreneurs and factors for development motivation of women entrepreneurs.